Psychological and quality of life outcomes following orthognathic surgery: A comprehensive systematic review - Alkaabi S; Alsabri G; Alyammahi A; Aljamani S; Maningky M; Helder M (Advances in Oral and Maxillofacial Surgery)
Orthognathic surgery (OGS) corrects functional malocclusions and enhances facial profiles. It is suitable for patients with dentofacial deformities, facial asymmetries, and craniofacial anomalies. OGS has significant psychological implications, making the assessment of patient satisfaction and quality of life (QoL) vital for optimal outcomes.This study evaluates the psychological context of patient satisfaction and QoL improvements post-OGS. A systematic review of 29 studies, following PRISMA guidelines, included databases like Cochrane, MEDLINE, and others. Results showed 25/29 studies reporting improved outcomes: OHIP (12/29), OQLQ (10/29), and SF-36 (7/29). Overall, OGS positively impacted QoL, emphasizing its effectiveness in psychological well-being and aesthetic transformation. Understanding limitations and exploring psychological impacts further can optimize patient outcomes.